The Natural Décade ""From War to Coexistence"" Towards a new vision of environmental ethics from the perspective of Michel Serres - benaouda, habib (Journal of Social Sciences and Humanities, 2021)
From this article we intend to get acquainted with the ecological philosophy and ideas of the French philosopher "Michel Serres", through researching the possibilities and limits of the natural contract proposed by this philosopher. It shows how the human ability to build and explore nature through the use of science and technology leads humanity to change the global destiny of mankind and the development of all other living beings on this planet. It is well known that the contemporary social and environmental crisis is also a cultural crisis that mainly relates to the way Western culture thinks and interferes with it. Consequently, this crisis goes far beyond the pollution of the atmosphere or the hole in the ozone layer. It involves risks that threaten humankind in its moral values, its outlook for the future and the limits of humanity, so it is a call to develop new ethics to limit mankind's technical control over all aspects of nature and the universe. Therefore, Michel serres calls for the restoration of nature as a matter of law by establishing a natural contract between man and nature to create a balance in a person's relationship with nature.